Axial deformation of early-age concrete-filled steel tubular columns under multi-stage loading - Tong, Donghua; Yu, Min; Li, Shulei; Zeng, Yanqin; Cheng, ShanShan; Chi, Yin (Structures (Oxford), 2023)
The continuous construction scheme for concrete-filled steel tubular structures in practice is time-saving and cost-effective in comparison to the conventional moulding construction methods, whilst this also results in complex stress conditions and working mechanisms in the early-age concrete-filled steel tubes (CFSTs) during construction. This investigation aims to explore the influence of continuous construction process on the axial compressive behaviour of early-age CFSTs as subject to multi-stage loading schemes. Eight short square early-age CFST columns are designed and tested. The axial deformation evolutions of CFSTs are analyzed for different load parameters including the initial stress of steel tube, loading time interval and load magnitude. The test results show that the deformation of early-age CFSTs varies significantly with various load parameters. Excessive deformation can be observed during the multi-stage loadings due to the local buckling of the steel tube. Based on the shrinkage and creep model of concrete, a theoretical algorithm for calculating the relationship between the deformation of early-age CFST and the age of concrete is developed. Furthermore, a simplified calculation method for the deformation of early-age CFST under multi-stage loading is proposed that can realistically describe the deformation of early-age CFSTs under continuous construction process. The research findings lay a foundation for the deformation control and safety assessment of CFST under continuous construction scheme.